2005
DOI: 10.1158/0008-5472.can-04-4526
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation-Induced Adenovirus Infection Is Mediated by Dynamin 2

Abstract: Specific viral targeting into intrahepatic tumors remains critical for adenovirus gene therapy in liver cancer. We previously showed that ionizing radiation increases adenovirus uptake and transgene expression in cells and colon cancer xenografts. Here, we tested whether radiation induces viral uptake through virus-cell membrane interaction. We found that radiation (8 Gy) induced adenoviral gene transfer in rat hepatocytes (WB) and human colon carcinoma cells (LoVo). This induction (24.4-and 6.5-fold, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…We and others have previously shown that IR increased oncolytic HSV-1 replication. [11][12][13][14][15][16][17][18][19][20][21][22][23] The hypothesis tested in this series of experiments was that if varying the timing of IR in relation to the timing of viral injection would result in a further enhancement of viral replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously shown that IR increased oncolytic HSV-1 replication. [11][12][13][14][15][16][17][18][19][20][21][22][23] The hypothesis tested in this series of experiments was that if varying the timing of IR in relation to the timing of viral injection would result in a further enhancement of viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23] Specifically, g 1 34.5 deleted HSV-1 combined with IR resulted in increased viral replication and glioma-xenograft regression in hindlimb and orthotopic preclinical murine glioma models. 11,17 Mechanistic studies have elucidated multiple pathways through which IR enhances viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to our previous finding that radiation induces adenovirus uptake in tumors by increasing the expression of dynamin 2, a membrane-bound GTPase that is important in a receptormediated internalization process, whereas coxsackie and adenovirus receptor is not changed by radiation. 17 In addition, it has been demonstrated that dynamin is crucial for liposome endocytosis and intracellular trafficking in neurons. 22 The role of dynamin 2 in radiation-induced liposome uptake is certainly worth further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Our own study has demonstrated that radiation induces adenovirus uptake in tumors, contributing to enhanced transgene expression. 16,17 For liposome-mediated delivery, radiation has been shown to increase drug delivery to tumor blood vessels 18 and to sustain an enhanced transgene expression in human breast cancer cells. 19 In addition, liposome-mediated delivery of the cytosine deaminase gene has resulted in radiosensitization of rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation